Pembuatan Booklet sebagai Media Informasi Bibliocrime di Perpustakaan Universitas Negeri Padang - Diri, Ulet Nata; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2019)
AbstractBibliocrime is caused by library user activities that can damage and harm the activities in the library. In order to reduce losses caused by Bibliocrime actions, prevention is carried out in order to improve the quality of services in the library and to reduce the number of damaged collections. One of them is by giving information and understanding to users that bibliocrime is included in acts of crime that can harm the library and other users. Therefore, the right tools are needed as a medium of information about Bibliocrime. Booklet as one of the information media is very useful to facilitate the delivery of information to users, with the booklet making it easier for users to understand what forms of crime should be avoided by users in the library, as well as what disadvantages caused by Bibliocrime activities and how how to prevent Bibliocrime actions. Booklets also facilitate librarians in delivering information, so librarians do not need to convey information directly because the booklet is an intermediary media in delivering information from librarians to users. Making booklets, namely: (1) needs analysis; (2) product design; (3)product manufacturing;Â booklet product manufacturing process is carried out.(4) product trial results; carried out to find out how the responses of librarians and librarians to the information contained in the booklet.Keywords: Bibliocrime, Booklet, LibraryÂ